DNA methylation is involved in acclimation to iron‐deficiency in rice (Oryza sativa). (15th June 2021) - Sun, Shuo; Zhu, Jiamei; Guo, Runze; Whelan, James; Shou, Huixia
SUMMARY: Iron (Fe) is an essential micronutrient in plants, and Fe limitation significantly affects plant growth, yield and food quality. While many studies have reported the transcriptomic profile and pursue molecular mechanism in response to Fe limitation, little is known if epigenetic factors play a role in response to Fe‐deficiency. In this study, whole‐genome bisulfite sequencing analysis, high‐throughput RNA‐Seq of mRNA, small RNA and transposable element (TE) expression with root and shoot organs of rice seedlings under Fe‐sufficient and Fe‐deficient conditions were performed. The results showed that widespread hypermethylation, especially for the CHH context, occurred after Fe‐deficiency. Integrative analysis of methylation and transcriptome revealed that the transcript abundance of Fe‐deficiency‐induced genes was negatively correlated with nearby TEs and positively with the 24‐nucleotide siRNAs. The ability of methylation to affect the physiology and molecular response to Fe‐deficiency was tested using an exogenous DNA methyltransferase inhibitor (5‐azacytidine), and genetically using a mutant for domains rearranged methyltransferase 2 (DRM2), that lacks CHH methylation. Both approaches resulted in decreased growth and Fe content in rice plants. Thus, alterations in specific methylation patterns, directed by siRNAs, play an important role in acclimation of rice to Fe‐deficient conditions. Furthermore, comparison with other reports suggests this may be a universal mechanism to acclimate to limited nutrient availability. Significance Statement: In plants, iron (Fe) is an essential micronutrient, but little is known if epigenetic factors are involved in responding to Fe‐deficiency. Here, it is shown that widespread CHH hypermethylation directed by siRNAs occurred after Fe‐deficiency. Using exogenous application of a DNA methyltransferase inhibitor 5‐azacytidine and a genetic mutant reduced in CHH methylation resulted in decreased Fe content and growth in rice plants.